Incorporating anti-infective drugs into peripherally inserted catheters does not reduce infection rates in neonates - Koppitz, Julia; Ascherl, Rudolf Georg; Thome, Ulrich Herbert; Pulzer, Ferdinand (Frontiers in Pediatrics, 2024)
Purpose This study assesses whether peripherally inserted central venous catheters (PICC), impregnated with anti-infective drugs, reduce the rate of infections in neonates compared with unimpregnated catheters. Methods A retrospective analysis was conducted on electronic patient records of neonates born between August 2014 and May 2020, who had PICCs inserted, either standard (S-PICC) or with anti-infective drugs (A-PICC). Catheter-related bloodstream infections (CRBSI) were diagnosed based on clinical symptoms, laboratory results, and mentioning of infection in the patient record. Data on dwell time, mechanical ventilation, insertion site, maximum C-reactive protein (CRP) concentration, and anti-infective drug use were analyzed. Results A total of 223 PICCs were included. The infection rates were A-PICC (18.9%) and S-PICC (12.5%), which were not significantly different (p = 0.257). A-PICCs had significantly longer dwell times than S-PICCs (median 372 vs. 219 h, p = 0.004). The time to infection was not different between the groups (p = 0.3). There were also no significant differences in maximum CRP, insertion site abnormalities, or anti-infective drug use between the groups. Conclusion This retrospective study did not find a significant reduction in infection rates by using PICCs containing anti-infective drugs in neonates. Current antibiotic impregnations do not seem to be effective in preventing blood stream infections.